2011
DOI: 10.1007/s00127-010-0337-5
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–compulsive disorder in the community: 12-month prevalence, comorbidity and impairment

Abstract: Background Although subthreshold conditions are associated with impairment in numerous disorders, research on obsessive-compulsive disorder (OCD) below the diagnostic threshold of DSM-IV in the general population is limited. Purpose To estimate the DSM-IV 12-month prevalence, comorbidity and impairment of OCD, subthreshold OCD (i.e., fulfilling some but not all core DSM-IV criteria), and obsessive-compulsive symptoms (OCS) (i.e., endorsement of OCS without fulfilling any core DSM-IV criteria) in a general popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 54 publications
3
97
2
4
Order By: Relevance
“…Given that OCS are not exclusive to OCD, occurring even in people without any psychiatric disorder, recent community surveys [20,[38][39][40] have adopted a dimensional approach to evaluate the occurrence of OCS, including subclinical manifestations, rather than a categorical view (i.e., presence or absence of OCD diagnosis).…”
Section: Factors Associated With Overall and Dimensional Ocs Severitymentioning
confidence: 99%
“…Given that OCS are not exclusive to OCD, occurring even in people without any psychiatric disorder, recent community surveys [20,[38][39][40] have adopted a dimensional approach to evaluate the occurrence of OCS, including subclinical manifestations, rather than a categorical view (i.e., presence or absence of OCD diagnosis).…”
Section: Factors Associated With Overall and Dimensional Ocs Severitymentioning
confidence: 99%
“…Among BD study populations, studies that only focused on BD-I, BD-II or BD Non Otherwise Specified (Angst et al, 2004) were included. Studies that considered subjects with bipolar and obsessive-compulsive spectrums were also included if diagnostic criteria used were specified (Angst et al, 2004, Adam et al, 2012. Participants of both sexes older than 6 years of age were considered.…”
Section: Study Population and Study Designmentioning
confidence: 99%
“…Two populationbased studies conducted, respectively, in USA and Germany, reported 6% and 10% of lifetime prevalence of comorbid BD in OCD adults (46,47) and 5% in OCD children and adolescents (46). Using the bipolar spectrum concept in the general population (48), a study reported 53.3% and 30% of BD-OCD and BD-II-OCD patients respectively (15).…”
Section: Included Studiesmentioning
confidence: 99%